2019
DOI: 10.1080/20008198.2019.1606625
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime traumatic stressors and adverse childhood experiences uniquely predict concurrent PTSD, complex PTSD, and dissociative subtype of PTSD symptoms whereas recent adult non-traumatic stressors do not: results from an online survey study

Abstract: This retrospective survey study compared the differential risk of lifetime traumatic stressors, so-called "non-traumatic stressors" experienced over the past year, referring to life events that do not meet the criteria for A1 traumatic events, and adverse childhood experiences (ACE) on severity of DSM-5 versus ICD-11 PTSD, Complex PTSD (CPTSD), and dissociative subtype of PTSD (D-PTSD) symptoms among 418 participants recruited online. In pairwise analyses, all stress types were associated with all outcomes. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 48 publications
7
63
0
1
Order By: Relevance
“…For the purposes of analysing the intensity of symptoms, the average score on each cluster is reported with the possible range from 0 to 4. Initial evidence supports the psychometric properties of the ITQ in different settings (Frewen et al, 2019;Ho et al, 2019). In our sample, the internal reliability measured by Cronbach's alpha was 0.77 for PTSD scale and 0.89 for CPTSD scale.…”
Section: The International Trauma Questionnaire (Itq)supporting
confidence: 78%
See 2 more Smart Citations
“…For the purposes of analysing the intensity of symptoms, the average score on each cluster is reported with the possible range from 0 to 4. Initial evidence supports the psychometric properties of the ITQ in different settings (Frewen et al, 2019;Ho et al, 2019). In our sample, the internal reliability measured by Cronbach's alpha was 0.77 for PTSD scale and 0.89 for CPTSD scale.…”
Section: The International Trauma Questionnaire (Itq)supporting
confidence: 78%
“…Although the ICD-11 proposes an association with specific types of stressors as risk factors rather than a requirement for development of CPTSD (Cloitre et al, 2018), considerable research has found childhood trauma to have significant impact on various outcomes in adulthood, particularly CPTSD (e.g. Frewen et al, 2019;Karatzias et al, 2019;Van der Kolk et al, 2019). The LEC-5 takes no explicit account of childhood trauma, which represents one of the major limitations of this measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elderly persons might be more distressed by measures of self-isolation than younger person due to fewer social contacts (Armitage & Nellums, 2020 ). Previous or current mental or physical health conditions (Liu, Chen, Lin, & Han, 2020 ) and previous trauma exposure (Frewen, Zhu, & Lanius, 2019 ) may be additional factors that may place people at greater risk. People who have COVID-19, or who have personal contact with people who may have COVID-19, are prone to mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…These effects are not specific and influence mental, physical, and physiological effects [1][2][3][4][5][6]. Some examples of the undesired effects of exposure to childhood trauma include anxiety [7], PTSD [8], depression [7], suicide [1,6], substance use [9][10][11], drug use [12], and mortality [1][2][3][4][5][6]. Childhood trauma also increases the risk of respiratory, heart, and metabolic diseases [13].…”
Section: Introductionmentioning
confidence: 99%